The Collaborative Governance Between Public and Private Companies to Address Climate Issues to Foster Environmental Performance: Do Environmental Innovation Resistance and Environmental Law Matter? - Sijing, Wei (Frontiers in Psychology, 2022)
In the recent decade, the environmental problem is increasing significantly worldwide. The decrease in environmental health, the environmental performance is decreasing continuously having adverse consequences for the societies. Therefore, to address the environmental problem in China, the current study examined the role of collaborative governance in environmental performance. Consequently, this study examined the relationship between collaborative governance, innovative methods, performance, availability of resources, environmental innovation resistance, environmental law and environmental performance. Both the public and private companies of environmental protection working in China are considered. To address the objective of the study, quantitative research approach is used along with the cross-sectional research design. A questionnaire survey is carried out among the public and private companies working in China for data collection. 290 valid questionnaires were returned and used in data analysis. Partial Least Square-Structural Equation Modeling (PLS-SEM) is used for data analysis. Results of the study reported important findings which has contribution to the literature and practice. Collaborative governance has major importance to enhance environmental performance. The collaboration between public and private companies has the potential to enhance environmental performance. It is found that; increase in collaborative governance can increase the innovative methods, performance and availability of resources which has the ability to enhance environmental performance. The improvement in innovative methods, performance and availability of resources can foster the environmental performance. Furthermore, environmental innovation resistance can decrease the environmental performance. Most significantly, environmental law is most crucial to enhance environmental performance. The better implementation of environmental law can enhance the environmental performance in China.